Crystal structure and infrared and Raman spectra of K3[Cr(CN)5NO].2H2O, a member of an iconic family of complexes in coordination chemistry - Piro, Oscar Enrique (2020)
Potassium pentacyanonitrosylchromate(I) dihydrate salt, K3[Cr(CN)5NO].2H2O, forms spontaneously from aqueous solution below about 15 °C while the anhydrous salt is obtained above 20 °C. The molecular structure of the dihydrate has been determined by X-ray diffraction, taking full advantage of modern data collection, advanced space group and structure solution and refinement. It crystallizes in the monoclinic space group Cc, is isomorphic to the Mn(I) analog, and shows the pseudo-symmetry of space super-group C2/c. The [Cr(CN)5NO]3− ion has an umbrella-like conformation with the equatorial Cr-CN bonds slightly bent away from the Cr-NO link. The crystallographic study fills a gap left in the literature on accurate structural data for alkaline and alkaline-earth salts of [M(CN)5NO]n- (M = V, Cr, Mn, Fe) series of coordination compounds. We also report here the solid-state vibration structure of the new compound, as probed by IR and Raman spectroscopy. Water mode assignments were assisted through deuterium enrichment. The thermal dehydration behavior complements structural and spectroscopic information on water molecules.